Advances in Databases and Information Systems : 24th European Conference, ADBIS 2020, Lyon, France, August 25–27, 2020, Proceedings /: 24th European Conference, ADBIS 2020, Lyon, France, August 25–27, 2020, Proceedings. (2020) - Unknown
No abstract available